2013
DOI: 10.13005/ojc/290250
|View full text |Cite
|
Sign up to set email alerts
|

Glutamic acid as an Efficient Catalyst for Synthesis of Dihydropyrimidinones

Abstract: A simple, efficient protocol for the one-pot Biginelli condensation reaction of aromaticaldehydes, β-ketoesters and urea employing glutamic acid as a novel catalyst is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…www.orientjchem.org it is possible to synthesize different polymorphs of calcium carbonate using dicarboxylic acids such as malonic acid, succinic acid etc as templating agents [13][14] . Another polycarboxylate was employed to synthesize calcite-micro trumpets [14][15][16] which closely mimic the coccoliths of an unicellular algae, Discosphaera tubifera.…”
Section: Oriental Journal Of Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…www.orientjchem.org it is possible to synthesize different polymorphs of calcium carbonate using dicarboxylic acids such as malonic acid, succinic acid etc as templating agents [13][14] . Another polycarboxylate was employed to synthesize calcite-micro trumpets [14][15][16] which closely mimic the coccoliths of an unicellular algae, Discosphaera tubifera.…”
Section: Oriental Journal Of Chemistrymentioning
confidence: 99%
“…Mimicking the design and synthesis of biominerals by living organisms is the current challenge for scientists [4][5][6][7][8][9][10] .Calcium carbonate is among the most studied biominerals because of its high abundance and ubiquity in nature. It is well established now that in case of calcium carbonate biominerals, templates with carboxylate groups are likely to direct structure through carboxylate moieties occupying carbonate sites during crystal growth and thereby directing the structure to produce the desired shape and functionality 11,13 . Our previous works have shown that by varying the concentration,…”
Section: Introductionmentioning
confidence: 99%
“…Thus, due to their several applications in the biology and medical chemistry, considerable interest in this transformation has steadily increased in the past decade and several improved procedures have recently been reported using Mg(NO 3 ) 2-6H 2 O [12], Al(NO 3 ) 3 Á9H 2 O [13], ZrCl 4 [14], zeolites [15], silica sulfuric acid [16], BF 3 ÁOEt 2 [17], CuCl 2 Á2H 2 O [18], SbCl 3 [19], RuCl 3 [20], natural catalysts [21], glutamic acid [22], Bi(NO 3 ) 3 [23], Bi 2 (SO 4 ) 3 Á3H 2 O [24], eutectic salts [25], NH 4 Cl [26], SiCl 4 [27], Y(OAC) 3 [28], Cu(OTf) 2 [29], FeCl 3 [30], NH 2 SO 3 H [31], B(OH) 3 [32], acidic ionic liquid [tbmim]Cl 2 /AlCl 3 [33], Bi(NO 3 ) 3 Á5H 2 O-silicagel [34], HCl [35], ZnBr 2 [36], Er(OTf) 3 [37], Phytic acid [38], Fe 3 O 4 MWCNT nanocomposite [39] and Fe 3 O 4 supported Brønsted acidic ionic liquids [40], Fe 3 O 4 supported sulfonated-phenylacetic acid coated [41], etc. Unfortunately, some of these methods are not environmentally friendly and suffer from one or more limitations, such as the use of strongly acidic conditions, prolonged reaction times, high reaction temperature, low to moderate yields of the desired product, tedious work-up, toxicity, and poor recovery and reusability of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Biginelli reaction suffers from low yields (20-50%) of products. Thus, in recent years, several methods to improve the use of Al(NO 3 ) 3 ⋅9H 2 O [13], ZrCl 4 [14], zeolites [15], silica sulfuric acid [16], BF 3 ⋅OEt 2 [17], CuCl 2 ⋅2H 2 O [18], SbCl 3 [19], RuCl 3 [20], natural catalyst [21], and glutamic acid [22] have been reported in the literature. However, some of these methods are expensive and harmful to the environment; stoichiometrically, the amount of catalyst, low yields, and incompatibility with other functional groups including product isolation methods is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, green chemistry has been defined as a set of principles that reduces or eliminates the use or generation of hazardous chemical materials. It is as part of our current studies on the development of new routes in heterocyclic synthesis [22].…”
Section: Introductionmentioning
confidence: 99%